Mathematics Reasoning Ability based on Personality Types on 9E Learning Cycle with Kid-Friendly Rubrics - Buwono, Iffah Sartika; Kartono, Kartono; Asih, Tri Sri Noor (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe learners' mathematical reasoning skills based on their personality types on the 9E learning cycle with kid-friendly rubrics. This research is mixed-method with a sequential explanatory design. The data collection of mathematical reasoning skills was done by using a test on four indicators. On the other hand, the data of personality types were taken by using KTS II inventory, documentation, and interview. The research subjects consisted of seventh graders of Private JHS Gema Buwana in 2020/2021. The findings showed that the learners' mathematics reasoning skills with guardian type could explain the model, fact, property, correlation, and pattern. These learners could use the correlation pattern to analyze the situation, create an analogy, and generalize. The artisan type could explain the model, fact, property, correlation, and pattern. They could create assumptions and evidence. The rational type could create a logical conclusion by explaining the model, fact, property, correlation, and pattern. They could also create assumptions and evidence, use the correlation pattern to analyze the situation, create an analogy, or generalize. On the other hand, the idealist type could explain the model, fact, property, correlation, and pattern. They could also make assumptions and evidence.